2011
DOI: 10.1021/jz2003606
|View full text |Cite
|
Sign up to set email alerts
|

Combined AFM−Confocal Microscopy of Oil Droplets: Absolute Separations and Forces in Nanofilms

Abstract: Quantitative interpretation of the dynamic forces between micrometer-sized deformable droplets and bubbles has previously been limited by the lack of an independent measurement of their absolute separation. Here, we use in situ confocal fluorescence microscopy to directly image the position and separation of oil droplets in an atomic force microscopy experiment. Comparison with predicted force vs. separation behavior to describe the interplay of force and deformation showed excellent agreement with continuum h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…[17] On the contrary, some repulsive surface forces, such as van der Waals forces, have been shown to further prevent the surfaces from collapsing or coalescing in order to maintain a minimum fluid thickness between them. [21] In a number of related studies, Chan and coworkers have developed a full numerical theory based on this analysis to describe the dynamic interactions of drops and bubbles measured using AFM (Fig. 3b).…”
Section: Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] On the contrary, some repulsive surface forces, such as van der Waals forces, have been shown to further prevent the surfaces from collapsing or coalescing in order to maintain a minimum fluid thickness between them. [21] In a number of related studies, Chan and coworkers have developed a full numerical theory based on this analysis to describe the dynamic interactions of drops and bubbles measured using AFM (Fig. 3b).…”
Section: Experimental Validationmentioning
confidence: 99%
“…[9,10] These deformations, in turn, can have a profound effect on the hydrodynamic interactions [11], such as those encountered during dynamic force measurements with the atomic force microscope (AFM) [12,13] or the surface forces apparatus (SFA) (see Figure 1b). [14,15] The SFA and AFM are well-suited to study the coupling between soft matter and hydrodynamic interactions, as demonstrated with droplets or bubbles [16][17][18][19][20][21] (Figure 1c(iii)). More recently, these tools have been employed and adapted to study elastohydrodynamic deformation of compliant solids.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation of the drops depends on their size, hydrodynamic interactions, colloidal forces, and surface forces [57,62]. According to recent emulsion stability simulations (ESS) an approximate threshold for drop deformation occurs around 2.5 µm [56,57,63,64].…”
Section: Flocculation Of Oil Dropsmentioning
confidence: 99%
“…29,35 Droplet deformation can be well predicted for viscous interfaces where droplet shape is described by the Young-Laplace equation. 29,32,[35][36][37][38][39][40] However, there is limited research which considers industrially relevant systems, such as water droplets in oil, 42 or interfaces with significant elasticity, for which the criterion of a Laplacian response no longer holds. 43 Our previous study 44 explored viscoelastic effects encountered in water-in-crude oil emulsion systems.…”
Section: Introductionmentioning
confidence: 99%